The Implementation of Guided Discovery-Based E-Worksheets on Students’ Mathematical Understanding Concepts and Independent Attitudes - Mafaza Aâ€™la, Muhammad; Junaedi, Iwan; Subali, Bambang (Universitas Negeri Semarang, 2021)
Students' mathematical understanding concepts are challenging enough to be explained virtually during distance learning. The study helps students to understand mathematical concepts and improve their independent attitudes. This study aims to analyze and describe the mathematical understanding concepts and independent attitudes of fourth grade students after the implementation of guided discovery-based e-worksheets in distance learning with synchronous and asynchronous patterns. The method used in this study is mixed-methods with an embedded experimental model design, true experimental pretest-posttest control group. The research population were all fourth-grade students from State Primary School 2 Jojo (experimental) and State Primary School 3 Jojo (control) in Kudus Regency. Sampling was determined by probability sampling technique, with a total of 23 fourth grade students at State Primary School 2 Jojo. Data collection techniques used test items, questionnaire instruments and document studies. The results of n-gain showed that the experimental class was 57% in the quite effective category compared control class of 41% in the less effective category. The results of independent sample t-test showed there was an average difference between two primary schools studied. The posttest average results of the experimental class were 80.43% compared control class of 72.69%, while the questionnaire average results of the experimental class was 77% compared to the control class was 73%. That means, the implementation of guided discovery-based e-worksheets is quite effective and can increase the mathematical understanding concepts and the independent attitudes of fourth grade primary school students.